Penerapan Transformasi Arsitektur Tradisional Buton pada Perancangan Cultural Center di Kabupaten Buton - Aldin Am Umar; Endang Setyawati; Akbar Preambudi (Archvisual: Jurnal Arsitektur dan Perencanaan, 2023)
Buton Regency is in Southeast Sulawesi, with a society that is thick with culture and traditions that have been passed down from generation to generation. However, along with technological developments, it has affected the interest of the Buton people in preserving local culture, especially in the younger generation who are starting to not care about local cultural values. The problem is, currently there is no place for the community of cultural activities and the place for the development of Butonese culture. One of the efforts to maintain local cultural values ​​is the need for a forum for cultural actors and the development of local culture, in the form of a cultural center building, which can also be used as a tourism support facility in Buton district. The purpose of this study is to develop a cultural center building design concept in Buton district with a traditional architectural transformation approach. This approach is intended so that the traditional values ​​of Butonese are realized in the architecture of the cultural center building, which can be a historical moment of traditional Buton architecture. The research method uses descriptive analytical methods, by uncovering existing data and analyzing it with the traditional Buton architectural transformation concept. The resulting design concept is a transformation of traditional architecture which is applied to: the mass layout; spatial patterns of Malige traditional houses; philosophy of mass forms; ornaments; and structures in the Malige Buton traditional house buildings.